Trade Costs and Foreign Direct Investment. - Neary, J (CEPR, 2006)
This paper reviews the theory of foreign direct investment (FDI), focusing on an apparent conflict between theory and recent trends in the globalized world. The bulk of FDI is horizontal rather than vertical, but horizontal FDI is discouraged when trade costs fall. This seems to conflict with the experience of the 1990s, when trade liberalisation and technological change led to dramatic reductions in trade costs yet FDI grew much faster than trade. Two possible resolutions to this paradox are explored. First, horizontal FDI in trading blocs is encouraged by intra-bloc trade liberalisation, because foreign firms establish plants in one country as export platforms to serve the bloc as a whole. Second, cross-border mergers, which are quantitatively more important than greenfield FDI, are encouraged rather than discouraged by falling trade costs.